2022
DOI: 10.1002/tox.23723
|View full text |Cite
|
Sign up to set email alerts
|

The role of stimulator of interferon genes‐mediated AMPK/mTOR/P70S6K autophagy pathway in cyfluthrin‐induced testicular injury

Abstract: Cyfluthrin is widely used in the field of sanitary pest control by its wide insecticidal spectrum, high efficiency and low toxicity, low residue, and good biodegradability. But, as a double‐edged sword, a large amount of cyfluthrin remains are still in the environment. The residual cyfluthrin is absorbed into the food chain through vegetation and then poses a risk to soil organisms and human health. Several studies have suggested that cyfluthrin is one of the main factors causing testicular damage, but the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…At present, at least three MAPK families have been identified: extracellular signal-regulated kinase 1/2 (ERK 1/2), c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (P38 MAPK) [ 24 ]. Our previous study showed that the expression of INHα and INHβB proteins in the testes of rats was reduced after being poisoned with Cy, suggesting that the testes may be the target organ of Cy toxicity, as, to some extent, it interferes with the normal secretion and function of male hormones, changes the hormone level and causes the stable state of the male reproductive endocrine system to break [ 25 ]. Therefore, the testicular spermatogenic function can be determined by the detection of reproductive hormones, and the normal signal transduction of the hypothalamus–pituitary–gonad axis is also strongly associated with the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…At present, at least three MAPK families have been identified: extracellular signal-regulated kinase 1/2 (ERK 1/2), c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (P38 MAPK) [ 24 ]. Our previous study showed that the expression of INHα and INHβB proteins in the testes of rats was reduced after being poisoned with Cy, suggesting that the testes may be the target organ of Cy toxicity, as, to some extent, it interferes with the normal secretion and function of male hormones, changes the hormone level and causes the stable state of the male reproductive endocrine system to break [ 25 ]. Therefore, the testicular spermatogenic function can be determined by the detection of reproductive hormones, and the normal signal transduction of the hypothalamus–pituitary–gonad axis is also strongly associated with the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of Cy, the potential health effects of Cy residues on soil organisms and human beings have become a hot issue [ 3 ]. The accumulation of Cy in the body causes disorders of the nervous system, digestive system, reproductive system, cardiovascular system and immune system [ 4 , 5 , 6 , 7 ]. Moreover, a previous research group found that approximately 57% of the investigated vegetable greenhouse growers used dangerous concentrations of Cy, which were higher than those of other pyrethroid insecticides used [ 8 ].…”
Section: Introductionmentioning
confidence: 99%